Menjadi Saksi di Tengah Diskriminasi: Tafsiran Daniel 1-6 dalam Bingkai Moderasi Beragama di Indonesia - Iskandar, Ferdinand; Panjaitan, Tutur (Sekolah Tinggi Teologi Berita Hidup, 2025)
The Indonesian context illustrates real religious discrimination, for example the prohibition of worship that is contrary to the law on freedom of worship, so the analogy with the story of Daniel and his three companions is relevant. They choose to be witnesses to their beliefs. Their rejection of oppression has an impact on the wider community. This paper presents an exegesis of Daniel 1-6 in the framework of religious moderation, which aims to explore how its narratives can provide a theological framework for Christians facing discrimination in Indonesia. The findings of the study suggest that the testimony model does not have to be confrontational, but rather rooted in three main pillars: relational obedience founded on the correct knowledge of God, flawless moral integrity, and surrender manifested through diligent prayer. This article implies how faith communities in Indonesia can appear as minority witnesses but have a public impact.